Prevalence of Depressive Symptoms and Associated Factors among HIV-Positive Youth Attending ART Follow-Up in Addis Ababa, Ethiopia - Helina Abebe; Shegaye Shumet; Zebiba Nassir; Melkamu Agidew; Dessie Abebaw (AIDS Research and Treatment)
Depression is most frequently and highly occurring common mental disorder in HIV/AIDS patients especially youth living with HIV/AIDS. This study aimed to assess the prevalence and associated factors of depressive symptoms among youth living with Human Immunodeficiency Virus (HIV) attending Antiretroviral Therapy (ART) follow-up at public hospitals in Addis Ababa, Ethiopia. Objective. To assess the prevalence and associated factors of depressive symptoms among youth living with Human Immunodeficiency Virus (HIV) attending Antiretroviral Therapy (ART) follow-up at public hospitals Addis Ababa, Ethiopia, 2016. Method. In a cross sectional study, 507 HIV-positive young people from public health hospitals were recruited by systematic random sampling technique. Beck Depression Inventory-II was used to assess depressive symptoms. Morisky medication adherence rating scale, social support rating scale, and HIV stigma scale were the instruments used to assess the associated factors. Results. Prevalence of depressive symptoms among HIV-positive youth was 35.5% (95% CI:31.3, 39.6). In multivariate analysis, age range between 20 and 24 years with (AOR=2.22, 95% CI: 1.33,3.62), history of opportunistic infection (AOR=1.94, 95% CI:1.15,3.27), poor medication adherence (AOR=1.73, 95%CI:1.13,2.64, low social support (AOR=2.74, 95%CI:1.13,2.64), moderate social support (AOR=1.75 95% CI: 1.03,2.98), and stigma (AOR=2.06, 95% CI: 1.35,3.14) were associated with depressive symptoms. The results suggest that prevalence of depressive symptoms among HIV-positive youth was high. Prevention of opportunistic infection, stigma, and counseling for good medication adherence are necessary among HIV-positive youth.